MicroRNA-21 Knockout Exacerbates Angiotensin II–Induced Thoracic Aortic Aneurysm and Dissection in Mice With Abnormal Transforming Growth Factor-β–SMAD3 Signaling. Issue 5 (May 2018) - Huang, Xiaofan; Yue, Zhang; Wu, Jia; Chen, Jiuling; Wang, Sihua; Wu, Jie; Ren, Linyun; Zhang, Anchen; Deng, Peng; Wang, Ke; Wu, Chuangyan; Ding, Xiangchao; et al.
Abstract : Objective—: Thoracic aortic aneurysm and dissection (TAAD) are severe vascular conditions. Dysfunctional transforming growth factor-β (TGF-β) signaling in vascular smooth muscle cells and elevated angiotensin II (AngII) levels are implicated in the development of TAAD. In this study, we investigated whether these 2 factors lead to TAAD in a mouse model and explored the possibility of using microRNA-21 ( miR-21 ) for the treatment of TAAD. Approach and Results—: TAAD was developed in Smad3 (mothers against decapentaplegic homolog 3) heterozygous (S3 +/− ) mice infused with AngII. We found that p-ERK (phosphorylated extracellular regulated protein kinases)– and p-JNK (phosphorylated c-Jun N-terminal kinase)–associated miR-21 was higher in TAAD lesions. We hypothesize that downregulation of miR-21 mitigate TAAD formation. However, Smad3 +/− :miR-21 −/− (S3 +/− 21 −/− ) mice exhibited conspicuous TAAD formation after AngII infusion. The vascular wall was dilated, and aortic rupture occurred within 23 days during AngII infusion. We then examined canonical and noncanonical TGF-β signaling and found that miR-21 knockout in S3 +/− mice increased SMAD7 and suppressed canonical TGF-β signaling. Vascular smooth muscle cells lacking TGF-β signals tended to switch from a contractile to a synthetic phenotype. The silencing of Smad7 with lentivirus prevented AngII-induced TAAD formation in S3 +/− 21 −/− mice. Conclusions—: Our study demonstrated that miR-21 knockout exacerbated AngII-induced TAAD formation in mice, which was associated with TGF-β signaling dysfunction. Therapeutic strategies targeting TAAD should consider unexpected side effects associated with alterations in TGF-β signaling. Abstract : Supplemental Digital Content is available in the text.